2015
DOI: 10.1007/s40265-015-0359-0
|View full text |Cite
|
Sign up to set email alerts
|

Secukinumab: First Global Approval

Abstract: Secukinumab (Cosentyx™) is a fully human monoclonal antibody against interleukin-17A, formulated for intravenous and subcutaneous administration. It received its first global approval in Japan on 26 December 2014 for the treatment of psoriasis and psoriatic arthritis in adults who are not adequately responding to systemic therapies (except for biologic agents). In the USA and the EU, secukinumab was approved in early 2015 for the treatment of patients with moderate-to-severe plaque psoriasis. Secukinumab is al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(72 citation statements)
references
References 21 publications
1
69
0
Order By: Relevance
“…T cells are more abundant in the synovial fluid of patients with PsA, compared to healthy individuals, and the levels of these cells positively correlate with measures of disease activity and joint damage progression [33] Fig. 1) [29,[36][37][38][39].…”
Section: The Il-17 Pathway In Psamentioning
confidence: 99%
“…T cells are more abundant in the synovial fluid of patients with PsA, compared to healthy individuals, and the levels of these cells positively correlate with measures of disease activity and joint damage progression [33] Fig. 1) [29,[36][37][38][39].…”
Section: The Il-17 Pathway In Psamentioning
confidence: 99%
“…For example, recent clinical trials have demonstrated a remarkable improvement of disease severity when IL-17A-and IL-17RA-targeting therapeutics are used (5,7,(39)(40)(41); and in January 2015, the first drug targeting IL-17A (secukinumab) was approved in the European Union and the United States for psoriasis treatment (8). In the imiquimod model, the expression of IL-17 signature genes such as S100a7a, S100a9, and Defb4 was only partially reduced in IL-17A-deficient mice, but highly reduced in IκBζ-deficient mice, also reflecting the inflammatory response seen in these mice as measured by ear thickness.…”
Section: Discussionmentioning
confidence: 99%
“…TNFα and IL-17A play a key role in disease pathogenesis, not only in psoriasis but also in other autoimmune diseases such as rheumatoid arthritis (4)(5)(6)(7). Whereas drugs targeting TNFα have been used in the treatment of these diseases for a number of years, secukinumab, an antibody targeting IL-17A, was just recently (January 2015) approved for the treatment of psoriasis in the European Union and the United States (8). Furthermore, in two phase III clinical trials, secukinumab has shown significant and sustained efficacy compared with placebo in patients with psoriatic arthritis (9).…”
mentioning
confidence: 99%
“…These reports apparently indicate that the blockade of the IL-17 or its receptors may yield better outcome compared to IL-23-targeted therapy. An antibody against IL-17A (secukinumab) was recently approved for the treatment of mild to moderate plaque psoriasis [90] (Table 1). Overall, on the basis of detailed understanding of the pathogenesis of various forms of GN and availability of appropriate therapeutic tools to verify whether these observations are indeed correct, delivering more targeted and less toxic treatment for GN is an achievable future aim.…”
Section: Resultsmentioning
confidence: 99%